Semantic explications of affixal word formation in the «Yrk Bitig» manuscript - Shaimerdinova Нурила; Dikhanbayeva Айгуль (Turkic Studies Journal, 2024)
The derivational subsystem of Turkic written monuments of the early Middle Ages in the semantic aspect has been insufficiently studied. The texts of medieval manuscripts show a wide range of word-formation possibilities, including compound bases, paired and affixed word-formation. The ‘Yrk Bitig’ is the only runic monument written on paper. Research has revealed that semantic relations are evident in the word-formation pair in affixal word formation. In word building, it is important to consider both the producing base and the word-formation affix used, taking into account the meaning of the affix. It is important to define the semantic relations between the derived base and the derived word. These relations are revealed through different types of motivations: direct, phraseological and semantically extended. This article analyses the corpus of word-forming affixes of the manuscript, classifying them based on their productivity and non-productivity. It determines their unique word formation meanings based on the system-forming function of the affixes and the preservation of some historical meanings. Direct motivation is common for both productive and non-productive affixes. However, the formation of names with the affix -laɣ/-lӓg/-laq/-lӓk is only phraseologically motivated. Names with the affixes -lïγ/-lig/-luγ/-lüg/-lïq and -(a)q/-(ӓ)k/-ïq/-ik/-uq/-ük have all three types of motivation.